Hypothyroidism: A Literature Review - Hardiant, Excell Defry; Adidaifa, Muhammad Fikri; Salsabila, Tsania Zulfa; Maulana, Muhammad Rafi; Salsabila, Baiq Ghefira Rojwani Putri; Untari, Lania Pradiva; Suryani, Elsa Indah; Paradiesta, Andi Frieskha Naurah; Savitri, Puti Amelia; Rahmat, Basuki (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Hypothyroidism is a condition in which the thyroid gland is unable to produce enough hormones to meet the body's needs. This condition causes a slowed metabolism, which can lead to various symptoms such as fatigue, weight gain, dry skin, hair loss, constipation, cold intolerance, and facial puffiness. Given the widespread impact of hypothyroidism and the potential for serious complications, special attention is needed for early detection, diagnosis, and effective treatment of hypothyroidism. This literature review was conducted using journal review methods and data searches through sources such as PubMed, Google Scholar, and ScienceDirect. The search used the keywords